2021
DOI: 10.1371/journal.pntd.0009788
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characterization of Lassa fever: A systematic review of clinical reports and research to inform clinical trial design

Abstract: Background Research is urgently needed to reduce the morbidity and mortality of Lassa fever (LF), including clinical trials to test new therapies and to verify the efficacy and safety of the only current treatment recommendation, ribavirin, which has a weak clinical evidence base. To help establish a basis for the development of an adaptable, standardised clinical trial methodology, we conducted a systematic review to identify the clinical characteristics and outcomes of LF and describe how LF has historically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 151 publications
1
17
0
1
Order By: Relevance
“…Up to 80% of patients infected with the Lassa virus will develop subclinical or mild disease, especially in endemic areas. After an incubation period of 1-3 weeks, characteristic pharyngitis, headache, vomiting and abdominal pain are observed as the main symptoms according to a recent systematic review (62). When progressing to the next stage (after 7 days), clinical hallmarks typically include facial oedema, neurological disorders, such as convulsions, encephalopathy, and bleeding.…”
Section: Clinical Signs and Symptomsmentioning
confidence: 99%
“…Up to 80% of patients infected with the Lassa virus will develop subclinical or mild disease, especially in endemic areas. After an incubation period of 1-3 weeks, characteristic pharyngitis, headache, vomiting and abdominal pain are observed as the main symptoms according to a recent systematic review (62). When progressing to the next stage (after 7 days), clinical hallmarks typically include facial oedema, neurological disorders, such as convulsions, encephalopathy, and bleeding.…”
Section: Clinical Signs and Symptomsmentioning
confidence: 99%
“…The earlier systematic review indicated that a low proportion of patients presented with these symptoms (except fever) on admission: sore throat– 44%; hearing loss– 4%; bleeding– 18%. [ 5 ] Due to potential low inclusions based on these criteria, the analysis team decided to raise this issue with the stakeholders at the next meeting.…”
Section: Resultsmentioning
confidence: 99%
“…[2] Symptoms are often non-specific and most commonly include fever alongside headache, vomiting and abdominal pain, with a small proportion of patients presenting with clinically severe, life-threatening symptoms, such as seizure, breathing difficulty and shock. [4,5] In hospitalised cases, the case fatality rate (CFR) is reported to be 24-27% [6,7] overall and 34% for pregnant women [8]-however in a recent cohort study taking place in a research setting, the CFR for hospitalised cases was 13% for adults and 6% for children. [9] Despite a weak evidence base, the primary treatment for LF is ribavirin in conjunction with supportive care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Merson, Bourner, Jalloh, Erber, Sallam, Flahault & Olliaro [6] extracted, verified, and summarized some primary clinical investigations and reports of patients with Lassa fever, both suspected and confirmed in some selected published works using descriptive statistics. Most of the data were from Nigeria and their findings showed that the main symptoms of Lassa fever include: gastrointestinal sickness, as well as other neural system and musculoskeletal issues that aren't usually considered Lassa Fever symptoms.…”
Section: Introductionmentioning
confidence: 99%